PENGARUH TATA RUANG KANTOR TERHADAP EFISIENSI KERJA PEGAWAI PADA KANTOR KECAMATAN DAMAI KABUPATEN KUTAI BARAT - Winandi, Teguh (PREDIKSI, 2014)
ABSTRACTÂ This Research want to know interior have effect to efficiency work the officer. To get the data needed a writer perform esearch in Office of Subdistrict of Damai of Regency of Kutai Barat.From provable research result that there are influence of variable of planology and efficiency variable work the officer. The mentioned proven from result data analyze by using statistic of rank correlation produck moment shown r = 0.99 meaning there are positiveÂ To more to improving of efficiency work the officer, beside factor of office planology hence factors of[is other;dissimilar require to get the attention, so that efficiency work the officer mounted can be improved again.